Perspectives for Biochar as a vehicle for inoculation of phosphate solubilizing bacteria: a review (Research, Society and Development, 2022)
Phosphorus (P) plays a vital role in many aspects of plant growth and development. The low amount of available P in agricultural soils reduces crop productivity and phosphate fertilizers are often applied. However, due to the high affinity of P for the soil constituents, the availability of this element becomes limited to plants. Thus, alternative, ecological, and low-cost techniques have been studied to improve P acquisition by crops. Microorganisms able to solubilize P, mainly phosphate-solubilizing bacteria (PSB) have stood out, since they offer an approach to overcome P scarcity by their introduction in agricultural systems via inoculants. In this paper, we showed the potential of P-solubilizing microorganisms and their mechanisms of action, the potential of different inoculation vehicles, also highlighting the biochar as a viable biological product for production of inoculants. The combined effects of these factors (PSB and biochar) add several benefits to the soil-plant system. Results from this review demonstrate that biochar amendments have great potential as a vehicle for inoculation of PSB. However, studies of biochar combined with PSB is still incipient. Future research should focus efforts on exploring highly efficient strains, optimizing conditions, and assessing several sources of waste for production of biochar and their efficiency in field experiments.